A Modified Synthesis of the Antiosteoporosis Drug Alfacalcidol via a Key Photochemical Transformation of 1α-5,6-trans-Vitamin D3 - Ding, Junyuan; Guo, Xianghai; Zeng, Zhouliangzi; Liu, Ningzhi (Synlett, 2013)
Alfacalcidol (1α-hydroxyvitamin D3) is an important clinical drug for the treatment of osteoporosis. Its practical synthesis has been intensively pursued across academia. The difficulties of separating 5,6-cis and 5,6-trans isomers in the current process was avoided by photochemical transformation of the 5,6-trans isomer into the 5,6-cis isomer. Employing vitamin D3 as a starting material, alfacalcidol was obtained by a five-step reaction sequence of esterification, cyclization, oxidation, solvolysis ring-opening, and subsequent photochemical reaction. The overall yield has been greatly improved from 17% to 31%.
Keywords: antiosteoporosis drug; vitamin D3; photochemical transformation